A 10-week FIFA 11+ program improves the short-sprint and modified agility T-test performance in elite seven-a-side soccer players - Foqha, Batool Mohammed; Schwesig, René; Ltifi, Mohamed Amine; Bartels, Thomas; Hermassi, Souhail; Aouadi, Ridha (Frontiers in Physiology, 2023)
Objective: Our primary objective in this study was to assess the effects of 10 weeks of the FIFA 11+ training on physical performance in elite seven-a-side soccer players. Methods Twenty-five seven-a-side soccer players were recruited from two senior national teams. The players completed, during 10 weeks, the following protocols a) FIFA11+: FIFA Group (n = 13) trained the FIFA 11+ program associated with regular soccer training; b) dynamic conventional warm-up: Control Group (n = 12) did their regular soccer training. They were tested twice in a pre-test followed by a post-test to measure the sprint performance (5 m, 10 m, 20 m sprint), Modified agility T-Test (MAT) and Five jump test (FJT). Results: The pre-post warm-up comparison for physical performance in each group demonstrated that in FIFA Group, the FIFA11+ significantly improve the 10 m sprint (p = 0.034; F = 5.04; ηp2 = 0.17) and the MAT (p = 0.000; F = 23.16; ηp2 = 0.52) when comparing with the Control Group, but without significant changes in 5 m, 20 m sprint and in FJT. Conclusion: The main findings of this research showed that the 10 week FIFA 11+ program led to significant improvements in the 10 m sprint and the MAT, compared to regular training among elite seven-a-side soccer players. Given these positive outcomes, further studies on practical implementation and optimization of the FIFA 11+ program are warranted to provide valuable guidance for coaches and athletes seeking to maximize its benefits in real-world settings.